Poor mobilization of autologous CD34+ peripheral blood stem cells in haematology patients undergoing autologous stem cell transplantation is associated with the presence of variants in genes implicated in clonal haematopoiesis of indeterminant potential. (22nd January 2021) - Gifford, Grace; Hesson, Luke; Wong, Jason W. H.; Carroll, Adam; Gabrielli, Sara; Bai, LiJun; Xia, Wei; Stevenson, William; Greenwood, Matthew
Summary: Clonal haematopoiesis of indeterminant potential (CHIP) increases in frequency with age. The effect of CHIP on the mobilization of autologous CD34+ peripheral blood stem cells (PBSC) has not been reported. This study uses a DNA‐based targeted candidate gene approach to identify the presence of somatic mutations in ASXL1, DNMT3A, JAK2, SF3B1, TET2 and TP53 in CD34+ haematopoietic progenitor cell‐apheresis products of 96 patients who undergo PBSC mobilization for autologous stem cell transplantation (ASCT). Variants were identified in a significantly greater proportion of patients who experience poor CD34+ PBSC mobilization. A DNA‐based targeted candidate gene array is able to predict poor CD34+ PBSC mobilization and may be deployed pre‐emptively to minimize mobilization and graft failures.